Low Temperature Effect on the Endocrine and Circadian Systems of Adult Danio rerio - Cristhian D. Sua-Cespedes (Frontiers Media S.A., 2021)
The control of the biological rhythms begins with the activation of photo- and thermosensitive cells located in various organs of the fish such as brain, eye, and skin, but a central clock is still to be identified in teleosts. Thermal changes are stressors which increase cortisol and affect the rhythm of other hormones such as melatonin and growth hormone (GH), in both endo- and ectothermic organisms. Our aim was to investigate how temperature (23°C for 6 days) lower than the optimal (28°C) modulates expression of several gene pathways including growth hormone (gh1) and its receptors (ghra, ghrb), insulin-like growth factor1 (igf1a, igf1b) and its receptors (igf1ra, igf1rb), cortisol and its receptor (gr), the limiting enzyme of melatonin synthesis (arylalkylamine N-acetyltransferase, aanat) and melatonin receptors (mtnr1aa, mtnr1bb), as well as their relationship with clock genes in Danio rerio in early light and early dark phases of the day. Lower temperature reduced the expression of the hormone gene gh1, and of the related receptors ghra, ghrb, igf1ra, and igf1rb. Cortisol levels were higher at the lower temperature, with a decrease of its receptor (gr) transcripts in the liver. Interestingly, we found higher levels of aanat transcripts in the brain at 23°C. Overall, lower temperature downregulated the transcription of hormone related genes and clock genes. The results suggest a strong correlation of temperature challenge with the clock molecular mechanism and the endocrine systems analyzed, especially the growth hormone and melatonin axes, in D. rerio tissues.